Persepsi Guru Terhadap Kinerja Kepala Sekolah di SD Negeri 71 Banda Aceh - Yenny Nadia; Sulaiman Sulaiman; M. Yamin (Elementary Education Research, 2023)
The teacher's perception of the performance of the principal at SD Negeri 71 Banda Aceh, Banda Raya District, Banda Aceh City can be viewed from the aspect of personality, the principal's knowledge of education staff, understanding of the school's vision and mission, decision-making ability and communication skills. As for the formulation of the problem in this study, how is the teacher's perception of the performance of the principal at SD Negeri 71 Banda Aceh? This study aims to describe teachers' perceptions of the performance of principals at SD Negeri 71 Banda Aceh.The approach used in this research is a qualitative approach with a descriptive research type. The subjects used in this study were 6 teachers. Collecting data in this study using interview techniques. To analyze research data, researchers used data reduction techniques, data presentation, and conclusions.The results of research at SD Negeri 71 Banda Aceh every time they want to make an internal decision the school always holds meetings and consults with the teachers to find the best solution for the school, always works together in carrying out any matter, is also always wise in making decisions by the principal and all teachers and staff are always compact, working together to advance the school. Meanwhile, to make decisions external to the school, the principal holds meetings and consults with teachers, committees and student guardians and also always asks for solutions and gives good suggestions.From the results of the study it can be concluded that at SD Negeri 71 Banda Aceh it was found that the teacher's perception of the performance of the principal was very necessary as a reference for the principal in analyzing his performance to build a better school and the results of interviews with the six teachers regarding the performance of the principal could be categorized already well. The principal has been able to carry out his duties as a leader and is very responsible and wise in all matters, be it discipline and good cooperation